Analysis of rainfall variations and coffee production areas with climate change in Minas Gerais via future scenarios - Carvalho Júnior, Flávio Vanoni de; Alves, Marcelo de Carvalho; Carvalho, Luiz Gonsaga de (Theoretical and applied climatology, 2024)
Rainfall is one of the main climatic variables capable of significantly interfering in the dynamics of human society. The knowledge about its behavior, as well as future changes in distribution, quantity and intensity has fundamental importance in the context of climate change and agricultural production. We aimed to identify the current distribution of rainfall and assess possible impacts of future variations in the state of Minas Gerais with a focus on coffee producing areas in the state. Historical and future rainfall data from the CMIP6 CNRM-ESM2-1 model were analyzed for the periods 2021-2040, 2041-2060, 2061-2080, and 2081-2100, under the SSP126 scenario, 2.5 minutes spatial resolution. Historical precipitation data from the period 1970-2000 were considered at the same spatial resolution to characterize the current rainfall regime. The spatio-temporal distribution of current and future monthly precipitation for monthly accumulations and annual totals was characterized by mapping, statistics, and annual rainfall volume difference between future and current periods. The relationship of coffee regions with areas subject to changes in precipitation was evaluated in relation to future scenarios. Changes in the beginning and end of the rainy season, as well as a future process of reduction in annual accumulations were observed in most of the state, with the eastern and northeastern portions being the most vulnerable. Most of the coffee producing municipalities in the state are located in areas with annual rainfall reduction in future scenarios.